2022
DOI: 10.1186/s13068-022-02233-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two 1,3-β-glucan-modifying enzymes from Penicillium sumatraense reveals new insights into 1,3-β-glucan metabolism of fungal saprotrophs

Abstract: Background 1,3-β-glucan is a polysaccharide widely distributed in the cell wall of several phylogenetically distant organisms, such as bacteria, fungi, plants and microalgae. The presence of highly active 1,3-β-glucanases in fungi evokes the biological question on how these organisms can efficiently metabolize exogenous sources of 1,3-β-glucan without incurring in autolysis. Results To elucidate the molecular mechanisms at the basis of 1,3-β-glucan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…β-1,3-Glucanases are PR-2 pathogenesis-related proteins, , which are strongly induced when plants respond to infection by bacterial, fungal, or viral pathogens. Previous studies indicated that β-1,3-glucanase can affect distortion during fruit growth and induce plant resistance to pathogenic fungi. Since β-1,3-glucan is a constituent polysaccharide of the fungal cell wall, β-1,3-glucanase can destroy the fungal cell wall and, thus, inhibit fungal infection. Furthermore, the oligosaccharide hydrolysates of β-1,3-glucanase act as an elicitor to activate the immune signaling response of the plant. , In this work, after treatment with BsGlc157A solution, the mycelial growth of three pathogenic fungi (C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-1,3-Glucanases are PR-2 pathogenesis-related proteins, , which are strongly induced when plants respond to infection by bacterial, fungal, or viral pathogens. Previous studies indicated that β-1,3-glucanase can affect distortion during fruit growth and induce plant resistance to pathogenic fungi. Since β-1,3-glucan is a constituent polysaccharide of the fungal cell wall, β-1,3-glucanase can destroy the fungal cell wall and, thus, inhibit fungal infection. Furthermore, the oligosaccharide hydrolysates of β-1,3-glucanase act as an elicitor to activate the immune signaling response of the plant. , In this work, after treatment with BsGlc157A solution, the mycelial growth of three pathogenic fungi (C.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that β-1,3-glucanase can affect distortion during fruit growth and induce plant resistance to pathogenic fungi. 33−35 Since β-1,3-glucan is a constituent polysaccharide of the fungal cell wall, 36 β-1,3-glucanase can destroy the fungal cell wall and, thus, inhibit fungal infection. Furthermore, the oligosaccharide hydrolysates of β-1,3-glucanase act as an elicitor to activate the immune signaling response of the plant.…”
Section: ■ Discussionmentioning
confidence: 99%
“…MALDI-MS analysis was performed according to Scafati et al (2022) with modifications. MS spectra of the sodium adducts of oligosaccharides [M + Na] + were performed with an UltraFlex MALDI-TOF/TOF mass spectrometer (Bruker, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…All of these glucanases have a specific modifying function, some removing glucose from the end, and others increasing the β-glucan branching system of the fungus, making the fungus more resistant to its own hydrolysis activity. This characteristic enables the fungus to feed on glycannic nutrients without damaging the organism, thus justifying the specific interest for P. expansum glucanases [28].…”
Section: Introductionmentioning
confidence: 99%